2020
DOI: 10.1002/jts.22618
|View full text |Cite
|
Sign up to set email alerts
|

Residential Cognitive Processing Therapy Decreases Suicidality by Reducing Perceived Burdensomeness in Veterans with Posttraumatic Stress Disorder

Abstract: The interpersonal theory of suicide (Joiner, 2005) may help explain high suicide rates among veterans with posttraumatic stress disorder (PTSD). It suggests that suicidal ideation results from believing that one is a burden on others (i.e., perceived burdensomeness) and does not belong among family, friends, or other social groups (i.e., thwarted belongingness). Evidence‐based PTSD treatments, including cognitive processing therapy (CPT), decrease suicidal ideation, potentially through changes in these two the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Overall patterns of outcomes remained the same regardless of the format in which CPT was delivered (i.e., massed or daily treatment, weekly, individual, or group), trauma type, or to whom it was delivered, although the populations within studies were predominantly military personnel and/or veterans (Blain et al., 2020; Bryan et al., 2018; Resick et al., 2017; Stayton et al., 2019; Johnson et al., in press; Holliday et al., 2018; Horwitz et al., 2018; Roberge et al., 2021; Bryan et al., 2016; Resick et al., 2015). One study included civilians (Johnson et al., in press), and another study looked at women rape survivors only (Gradus et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall patterns of outcomes remained the same regardless of the format in which CPT was delivered (i.e., massed or daily treatment, weekly, individual, or group), trauma type, or to whom it was delivered, although the populations within studies were predominantly military personnel and/or veterans (Blain et al., 2020; Bryan et al., 2018; Resick et al., 2017; Stayton et al., 2019; Johnson et al., in press; Holliday et al., 2018; Horwitz et al., 2018; Roberge et al., 2021; Bryan et al., 2016; Resick et al., 2015). One study included civilians (Johnson et al., in press), and another study looked at women rape survivors only (Gradus et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…There were 11 studies that included CPT. Eight studies examined CPT only (Blain et al., 2020; Bryan et al., 2018; Resick et al., 2017; Stayton et al., 2019; Johnson et al., in press; Holliday et al., 2018; Horwitz et al., 2018; Roberge et al., 2021) and three studies compared CPT to another EBT (Bryan et al., 2016; Gradus et al., 2013; Post et al., in press; Resick et al., 2015). Ten CPT studies showed reductions in both PTSD‐ and suicide‐related outcomes, with the majority reporting significant reductions and, generally, few or no reports of suicidal ideation or behaviors at posttreatment or follow‐up assessments.…”
Section: Resultsmentioning
confidence: 99%
“…Trials could also compare augmenting medications to nonpharmacological interventions, such as psychosocial stabilization interventions and evidence‐based psychotherapy for PTSD, which do not carry the health risks of medication 41,42 . Evidence‐based psychotherapy for PTSD has been found to help improve complex symptoms such as suicide risk and psychotic symptoms 43–46 . Thus, clinicians may consider offering these treatments to patients as soon as possible to help prevent crisis situations as well as improve PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Evidence-based psychotherapy for PTSD has been found to help improve complex symptoms such as suicide risk and psychotic symptoms. [43][44][45][46] Thus, clinicians may consider offering these treatments to patients as soon as possible to help prevent crisis situations as well as improve PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some anecdotal reports from returning veterans suggest that the loss of perceived usefulness and the meaningful role derived from their military service is integrally implicated in the loss of a sense of having a life worth living. The subsequent article by this research team takes a translational bent by examining whether directly addressing these maladaptive appraisals improves outcomes for traumatized veterans under treatment (Blain et al., 2021). The results show that, among veterans undergoing cognitive processing therapy (CPT) for PTSD, treatment‐related changes in levels of PTSD symptoms and negative self‐cognitions were associated with reduced suicidal ideation.…”
mentioning
confidence: 99%